Perilaku Sosial Pengurus Badan Eksekutif Mahasiswa Dalam Perspektif Etika Berorganisasi di Tingkat Universitas Palangka Raya - Wawan Nopardo Andika Saputra; Eddy Lion; U. Z. Mikdar (FKIP, Universitas Palangka Raya, 2023)
The existence of student organizations in tertiary institutions is important in the context of self-development of students themselves. This is confirmed by the Law of the Republic of Indonesia Number 12 of 2012 concerning Higher Education article 77 concerning Student Organizations. There is an imbalance in the ideal organizational paradigm with field facts, the benefits of participating in the BEM UPR organization, the bargaining value of BEM UPR at the external level, as well as perceptions of BEM UPR's social behavior and organizational ethics, became the basis for researchers interested in studying by taking the title of the final project with the theme of ethics, namely